Development of metrological support of process control system of injection molding of bimetallic castings - Савельева, Оксана Степановна; Прокопович, Игорь Валентинович; Шмараев, Александр Васильевич (Eastern-European Journal of Enterprise Technologies, 2015)
The paper describes the process flow diagram of the injection molding of bimetallic castings. It is shown that effective quality control of bimetallic castings "steel - aluminum" requires appropriate metrological support. The structural scheme of the automated process control system of injection molding of bimetallic castings was proposed. To measure the heating uniformity of the steel insert surface before aluminum casting and weldability completeness of these components, using images obtained with the thermal imager was proposed. Junction zone control was proposed to carry out using macrosection pictures in the junction zone. As a result, metrological evaluation of the thermal image of composite casting was performed using the Hausdorff-Besicovitch dimension. This has allowed to reduce the diversity of the information contained in the source image to a single number. This number reflects the characteristic features of the structure and allows the use for process management decision-making. Decrease in the rejection rate of castings in the actual production was experimentally confirmed.